Ascorbic acid quantification in Benincasa hispida fruit extracted using different solvents - Fatariah, Z.; Tengku Zulkhairuazha, T. Y.; Wan Rosli, W. I. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Ascorbic acid or vitamin C is mostly found in natural products such as fruits and vegetables. High performance liquid chromatography (HPLC) method has been developed and validated to compare the ascorbic acid content in Benincasa hispida (Bh) fruit extract with three different extraction solvents; i) 3% metaphosphoric acid, ii) 3% citric acid and iii) distilled water. The compound has been detected and quantified by the use of HPLC coupled with UV-Vis detector. The amount of ascorbic acid detected in Bh fruit extract prepared with different extraction solvents; 3% metaphosphoric acid, 3% citric acid and distilled water were 13.18, 7.91 and 9.42 mg/100g respectively. Total run time was 6 min and the retention time was 2.60 min. Calibration curve was linear with the concentration range 1.00 – 16.00 μg/ml. Limits of detection was 0.24 μg/ml, limit of quantification was 0.81 μg/ml and recovery was 93.52%. The result showed ascorbic acid content is higher in Bh fruit extract with 3% metaphosphoric acid, followed by extract with distilled water and 3% citric acid. Thus, Bh is another novel fruit/ vegetable potentially used as food ingredient as it contains a good source of ascorbic acid that can be good for one’s health.